Farmer processes of experimentation and innovation: a review of the literature - Saad, Nadine (2001)
‘Lay’ experimentation1 in agriculture and natural resource management dates as far back as the stone ages. It has led to the domestication of today’s crops and landraces, to the development of numerous traditional agricultural practices, and to the existence of a substantial body (or bodies) of Indigenous Knowledge. Something is happening in the field; farmers are not passive. Their cropping patterns and genetic materials are in a constant state of flux. They discriminate what they need from what is less useful. They actively test new and different ways of managing their natural resources; and they continuously apply selective pressures on their crops, and test materials obtained from natural crosses, or from other farmers. Often all this is done without the participation of formal research and extension systems.